Effect of anionic salts in concentrate mixture and magnesium intake on some blood and urine minerals and acid-base balance of dry pregnant cows on grass silage based feeding - Tauriainen, Susanna; Sankari, Satu; Pyörälä, Satu; Syrjälä-Qvist, Liisa (Agricultural Research Centre of Finland, 1998)
Tutkimuksessa selvitettiin ummessaolevien lehmien kationi-anionitasapainon alentamisen vaikutuksia, kun magnesiumin saanti oli joko suomalaisten kivennäisnormien (16 g Mg/pv, 0.2% kuiva-aineesta) tai hollantilaisten kivennäisnormien mukaista (33 g/Mg, 0.4% kuiva-aineesta). Kationi-anionitasapaino laskettiin [(Na+ + K+) - (Cl- + S2-)] mEq/kg kuiva-ainetta (ka). Se oli joko +340 tai +31 mEq/kg ka. Magnesiumlisä annettiin magnesiumoksidina. Suoloina käytettiin magnesiumkloridia, ammoniumkloridia ja -sulfaattia. Lehmät saivat säilörehua (5.2 kg ka), heinää (1.0 kg ka) ja täysrehua (1.5 kg ka) neljä viikkoa ennen odotettua poikimista poikimispäivään saakka. Veri- ja virtsanäytteitä otettiin 4, 3, 2 ja 1 viikkoa ennen odotettua poikimista, poikimispäivänä sekä 1 vrk ja 1 viikko poikimisen jälkeen. Tulosten mukaan magnesiumoksidista ei ollut hyötyä ummessolevien lehmien magnesiumlisänä. Nykyistä suomalaista magnesiumsuositusta tulisi silti tarkistaa, koska kokeessa ilmeni muutamia hypomagnesiatapauksia poikimisvuorokautena. +31 mEq/kg ka ei aiheuttanut muutoksia verestä ja virtsasta mitattuihin parametreihin. Se ainoastaan lisäsi kalsiumin eritystä virtsaan ja alensi virtsan pH-arvoa verrattuna positiivisempaan kationi-anionitasapainoon (+340 mEq/kg/ka). Näin ollen kationi-anionitasapaino tulisi säätää pienemmäksi, jotta siitä olisi hyötyä poikimisen aikaiseen kalsiumaineenvaihduntaan.

Twenty Friesian cows were randomly assigned to one of four prepartum diets in a 2 x 2 factorially designed experiment to determine the effect of anionic salts contained in a concentrate mixture and magnesium (Mg) intake on some blood and urine minerals in cows fed a grass silage based diet. Four diets provided either 16 g or 33 g total dietary Mg/day, and had either a low or high cation-anion difference. Dietary cation-anion balance (DCAB) of the diets, calculated as milliequivalents [(Na+ + K+) - (Cl- + S2-)], was +31 mEq/kg dry matter (DM) in the low DCAB group and +340 mEq/kg DM in the high DCAB group. DCAB was formulated using NH4Cl, (NH4)2SO4 and MgCl2 as anionic salts. Cows received grass silage (5.2 kg DM), hay (1.0 kg DM) and concentrate mixture (1.5 kg DM) until calving. Blood and urine samples were collected 4, 3, 2 and 1 week before the expected calving date, at calving, the day after calving and 1 week following calving. Cows fed the low DCAB diet had a lower urinary pH (P<0.05) and excreted more Ca in the urine (P<0.05) throughout the study. During the experimental period, Mg intake did not affect any parameters measured in plasma or urine. It was concluded that there was no benefit of additional Mg over Finnish recommendations (17 g Mg/d) when using MgO as a source of Mg for silage based diets. In addition, reducing DCAB within positive a range may not be sufficient, since urinary pH was relatively high and no changes in blood Ca2+ were observed.
Keywords: Ko; lehmät; magnesium; säilörehuruokinta; magnesium; calcium; cation-anion balance; cows; minerals; metabolism